Development of physical activity and food built environment quality indicators for chronic diseases in Argentina. (20th February 2021) - Seijo, Mariana; Spira, Cintia; Chaparro, Martín; Elorriaga, Natalia; Rubinstein, Adolfo; García-Elorrio, Ezequiel; Irazola, Vilma
Summary: Although obesity and non-communicable disease (NCD) prevention efforts to-date have focused mainly on individual level factors, the social and physical environments in which people live are now widely recognized as important social determinants of health. Obesogenic environments promote higher dietary energy intakes and sedentary behaviors, thus contributing to the obesity/NCD burden. To develop quality indicators (QIs) for measuring food and physical activity (PA)-built environments in municipalities. A literature review was conducted. Based on the best practices identified from this review, a draft set of candidate QI was retrieved. The initial 67 QIs were then evaluated by a modified Delphi panel of multidisciplinary health professionals ( n = 40) to determine their relevance, validity, and feasibility in 3 rounds of voting and threaded discussion using a modified RAND/University of California, Los Angeles Appropriateness Methodology. Response rate for the panel was 89.4%. All final 42 QIs were rated as highly relevant, valid, and feasible (median rating ≥ 7 on a 1–9 scale), with no significant disagreement. The final QI set addresses for the PA domain: (i) promotion of PA; and (ii) improvements in the environment to strengthen the practice of PA; and for Food environment domain: (i) promotion of healthy eating; (ii) access to healthy foods; and (iii) promotion of responsible advertising. We generated a set of indicators to evaluate the PA and food built environment, which can be adapted for use in Latin American and other low- and middle-income countries. Lay Summary: The built environment has a considerable effect on health indicators such as physical activity, eating behavior, and community. There is considerable research evidence demonstrating a direct relationship between our built environments and our health. In Argentina, the Healthy Municipalities and Communities Program focuses in health promotion interventions. It was developed to seek collaboration among community members, local government authorities and other stakeholders in order to improve quality of life. However, up to date, there has not been a homogenous measure to evaluate how well a particular locality or a whole municipality supports the health and wellbeing its residents. The proposed study aims to develop a set of local valid and common measures in order to evaluate what is happening within a particular municipality. A designated group of local experts will select a set of final measures trough out an iterative multistage process in order to combine opinion into group consensus. We will ask the panel to rate, discuss and re-rate the proposed measures (based on the existing evidence). This will study provide an evaluative tool to inform policy making and program implementation, and to guide programs and initiatives aimed at combating obesogenic environments in municipalities and communities.